Fractional-order position/force control of two cooperating manipulators - Ferreira, N. M. Fonseca (2003)
In this paper it is studied the implementation of fractional-order algorithms in the position/force control of two cooperating robotic manipulators. The system performance is analyzed in terms of time and frequency response for different operating condicitons.